Genetic variability in kacholam(kaempferia galanga L)under open and partially shaded conditions - Divya Krishnan (Department of Plant Breeding and Genetics, College of Agriculture, 2008)
A research programme was carried out at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during the period 2007-08 with the object of assessing the genetic variability in kacholam genotypes for yield and yield attributing characters. Data on the investigations were recorded from two field experiments- one under open and other under partially shaded conditions. Twenty two genotypes including two released varieties (Kasthuri and Rajani) were evaluated for yield and related characters in field experiments in RBD with three replications under open and partially shaded conditions in coconut garden. Analysis of variance revealed significant difference among the genotypes for all the 37 characters studied. Genotypic and phenotypic coefficients of variation were highest for volatile oil, dry weight of roots, and fresh weight of leaves and fresh yield of rhizome per plant under both conditions. Under both conditions, characters such as fresh yield of rhizome, dry yield of rhizomes, fresh weight of leaves, dry weight of roots, length of secondary rhizomes and volatile oil showed high heritability coupled with high genetic advance. Rhizome yield showed significant positive correlation with fresh weight of leaves, number of suckers per plant and length of mother rhizome under both the conditions. Leaf area ratio was found to be negatively correlated with rhizome yield under both open and partially shaded conditions. Volatile oil, dry yield of rhizomes per plant, fresh yield of rhizome per plant, dry weight of roots, fresh weight of roots had highest heritability and genetic advance under two conditions viz., open and partially shaded condition. The characters such as plant spread, fresh weight of leaves, dry weight of leaves, number of suckers per plant, length of mother rhizome, number of secondary rhizomes, length of secondary rhizome, girth of secondary rhizome fresh yield of rhizomes and dry yield of rhizomes found to be positively and significantly correlated with oil yield under both conditions. Path analysis revealed that harvest index, dry weight of roots and dry weight of leaves were the primary yield contributing characters due to their high direct effect on rhizome yield. Mahalanobis D2 analysis clustered the twenty two genotypes into seven clusters. Cluster VII formed the largest cluster with 10 genotypes while clusters I, II and III had one genotype each. The genetic distance was maximum between clusters III and V while minimum divergence was between clusters II and VI. The intra cluster distance was highest for cluster IV. Selection index revealed that the genotypes Neyyattinkara attained maximum selection index value followed by Koothattukulam and minimum estimates were recorded by Alleppey and Kasaragod. The genotypes from Neyyattinkara, Koothattukulam, Madavur, Ponneyekkad, Kannur, Ponnukara and Kanyakumari district and were superior in terms of yield and quality parameters as pure crop and as an intercrop in coconut plantations. So these genotypes can be considered for further crop improvement programme.